UPAYA DOSEN MENINGKATKAN MOTIVASI MAHASISWA PEMBELAJARAN BAHASA ARAB - Hayati, Mardhiyah (LPM Penalaran UNM, 2019)
Motivation is a way that is done by giving encouragement to students to be more enthusiastic and passionate in the learning process, especially in the field of Arabic studies. Motivation is an important thing to note because motivation can improve morale, loyalty, responsibility, discipline, creativity, and enthusiasm of students. The purpose of this paper is to determine the efforts of lecturers in providing motivation to students in learning Arabic. Arabic is a part of religion, and knowing that the law is obligatory, because actually understanding the Book and as-Sunnah is a matter that is mandatory, and can not be understood except with Arabic.The data used are primary data obtained through interviews and observations. The data obtained were analyzed using descriptive analysis method. After an analysis, it can be concluded that the Arabic language education lecturer at the Raudhatul Jannah Arabic Language Education Institute (LPBA RJ) has provided motivation to students. Motivation provided Types of motivation used are positive and negative motivations. Positive motivation in the form of appreciation, praise, or prizes. While negative motivation is in the form of a reprimand.